IMPLEMENTASI KEBIJAKAN PENGELOLAAN AIR BAWAH TANAH DI KOTA PEKANBARU TAHUN 2012-2014 - Riki Syaputra; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to identify and analyze the management of underground water in the city pekanbaru.persoalan arising in practice on pnelolaan underground water in the city of pekanbaru is licensing only partisan (not exhaustive) without control is also a real phenomenon discovered, almost all objects both individual and corporate policies almost no reported utilization of the amount of underground water to pemerintah.kondisi is caused also by weak supervision by pemerintah.pengelolaan underground water in more development leads to good commercial activity undertaken individuals and business entities .sehingga authors formulate this research is how the implementation of an underground water management policy in the city of pekanbaru in 2012-2014? What are the factors that affect the implementation of an underground water management policy in the city of pekanbaru in 2012-2014?.This type of research used in this research is kualitatif.lokasi this research is in the head office handsome, bukit raya subdistrict office and department of spatial planning and building in the city pekanbaru.dalam collect data sampling.purposive researchers used a technique purposive sampling is a sampling technique source data with particular consideration, for example, the person considered most knowledgeable about what is expected, so it will be easier for researchers to explore objects and social situation in teliti.untuk get the data in this study, the authors used data of observation, interviews, and documentation. Theory of policy implementation is a theoretical foundation in this study using a model of policy implementation grindle namely the emphasis on content and context aspects linkunganya. Based on the results of the study the factors that influence the implementation of an underground water management policy in the city of pekanbaru is the contents of the policy aspect is the interest affected by the policy, administration and eliminate motivation semakinmempersempit initial formation of the desired degree perda.akibatnya not optimal because the provincial government does not expressly and do not have the ability to manage up to his level terendah.serta eroded by the municipal government program policies more emphasis on it because the levy as well as information and clarity regarding the management of the policy are not detailed by a user pelaksanaannya.dari environmental context, which is a factor influencing the policy of regulation power and administrative factors.Keywords; management, policy, water resources, conservation